EFFECT OF ZINC AND BORON FOLIAR APPLICATION ON GROWTH, YIELD AND QUALITY OF SOME SUNFLOWER GENOTYPES ( Helianthus annuus L.) - Saad Al-Doori (Mesopotamia Journal of Agriculture)
A field experiment was conducted during spring and autumn growing seasons of 2009 to study the effect of foliar application of zinc and boron on growth characters, yield componentsand quality of some sunflower genotypes (Helianthus annuus L.). The experiment was carried out according to the factorial experiment in a randomized completely block design, consisting of three zinc application (0,  6, 12 mg.L-1) and three boron application (0, 4 and 8 mg.L-1) with three sunflower genotypes (Myogen, Isaanka and Ginmus). The main findings could be summarized as follows:- Foliar application of zinc to the leaves with concentration 12 mg.L-1 showed a significant increase in plant height, stem diameter, leaf area, head diameter, number of seeds head-1, 1000 seed weight and seed yield.ha-1, oil percentage, oil, protein yield (ton. ha-1), However, protein percent was decreased. Addition of boron sprayed on the plant leaves with concentration 4 mg.L-1 lead to a significant increase in plant height, stem diameter, leaf area, head diameter, number of seeds head-1, 1000 seed weight and seed yield.ha-1, oil percentage, oil, protein yield (ton.ha-1), while increasing concentration of boron to 8 mg.L-1 caused a significant increase in protein percentage in the two seasons'. Results showed that the Isaanka genotype gave a high values for characters stem diameter, leaf area, head diameter, number of seeds. head-1, 1000 seed weight and seed yield.ha-1, oil percentage, oil, protein yield (ton.ha-1) in both seasons. The triple interaction among Isaanka genotype × foliar application of 12 mg Zn.L-1 × concentration of 4 mg B.L-1 sprayed on the plant leaves, achieved the highest mean for the characteristics of: plant height, stem diameter, number of seeds head-1, seed yield.ha-1 and oil, protein yield (ton.ha-1) for both seasons. In general, it could be concluded that for maximizing total seed and oil yields per unit area may be achieved by planting Isaanka genotype with adding zinc and boron to the leaves plant with concentration 12 Zn and 4 B mg.L-1 under the environmental conditions of this study